PENGARUH KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP HUBUNGAN ANTARA PARTISIPASI ANGGARAN DENGAN SENJANGAN ANGGARAN - IVAN BUDI YUWONO (Jurnal Bisnis dan Akuntansi, 1999)
The relation between budgetary participation and budgetary slack has been examined in several accounting studies with conflicting result. The conflicting evidence may reflect the influence of a contingency variable. This study investigated the effect of organizational commitment and environmental uncertainty on the relationship between budget participation and budgetary slack. The responses of 70 managers, drawn from a cross-department in Indonesia, to a questionnaire survey, were analyzed by examining the multiple regression model. The result indicated that the high degree of budget participation was associated with higher budgetary slack under conditions of low environmental uncertainty. Under conditions of high environmental uncertainty, high degree of budget participation was associated with lower budgetary slack. This study also found that there were a positive relationship between budget participation and budgetary slack, and a positive relationship between environmental uncertainty and budgetary slack.